Age of Great Grey Owls Stirix nebulosa observed in Scandinavia in 2012 as revealed by digital photos in the national species report archives - Solheim, Roar (Ornis Svecica, 2014)
Record breaking numbers of breeding Great Grey Owls Strix nebulosa were reported in Sweden and Norway in 2010 and 2011, followed by 4,105 observations in 2012 as revealed by the national Species archives. Based on locality id numbers, at least 144 individuals were reported with photos which could be used to age the individuals. The majority (76%) of these birds were young birds hatched in 2011 (83% including birds aged probably 2CY). Among dead owls brought to the Natural History Museum in Stockholm, the percentages of owls hatched in 2011 were similar (78% and 88%). The high percentage of young owls could be caused by young birds hunting closer to human settlement than older birds, but more likely it was caused by a higher total production of young in south-central Scandinavia in 2011 than in 2010. This study shows that photos in the national species archives reveal the age structure of the Great Grey Owl population, fundamental data to understand the current distributional expansion of this species. This method may also be applied to other species.